Manual de caracterización genotípica de recursos genéticos - Biondi Thorndike, Jorge Andrés; Fernández Huaytalla, Elizabeth; Zorrilla Cisneros, Cinthya; Amasifuen Guerra, Carlos Alberto (Instituto Nacional de Innovación Agraria, 2021)
78 Páginas